The DevOps 2.2 Toolkit : Self-Sufficient Docker Clusters. - Farcic, Viktor (Packt Publishing, 2018)
Viktor Farcic's latest book, The DevOps 2.2 Toolkit: Self-Sufficient Docker Clusters, takes you deeper into Docker, teaching you with a mixture of theory and hands-on how to successfully build both self-adaptive and self-healing-based systems.